The impact of the use of ball exercises sense to learn some basic skills handball - Mahmoud, Mohammed (Journal of Physical Education, 2012)
The conclusion for this research that this sensitive training by using the ball made a huge effect to improve the performance skills level on handball also this way leads the student learning the basic skill in short time. The effect of using sensitive training by balls in learning some basic skills for handball. The researcher talking about there slower in learning for basic skill in handball for student that obligated the instructor that made west time in another skills the program completed in exact time .The first aims that using supposing exercise to improve sensitive level by using the balls for second stage in physical education. And the second aim to know the effect for using this exercise.